Effect of temperature on the development, reproduction and mortality of the sweetpotato weevil Cylas brunneus (Fabricius) (Coleoptera: Brentidae) - Musana, P.; Okonya, J.; Kyamanywa, S.; Kroschel, Jürgen (2013)
The sweetpotato weevil, Cylas brunneus, is a serious insect pest of sweetpotato (Ipomoea batatas(L.) Lam.) in East and West Africa. Knowledge on the influence of temperature on development, reproduction and mortality of this pest is important in understanding its potential population growth and geographical distribution. Such knowledge is a pre-requisite for developing pest control strategies for different agro-ecological zones. The effect of temperature on the development of immature stages, reproduction and mortality of C. brunneus was studied at six constant (15, 20, 25, 30, 35 and 40 °C) and at fluctuating temperature range of 22.9 ± 8.7 °C. Results obtained indicated that at 15°Cand 40 °C, there was no development and reproduction of C.brunneus. At 35°C, only 46 % of eggs hatched after 1.78 ± 0.20 days but the larvae from these eggs did not pupate. Egg-laying was not possible at 15 °C, 35 °C and 40 °C. The developmental period from egg to adult at 15 °C, 20 °C, 30 °C and 35 °C was 59.43 ± 2.17 days, 49.00 ± 0.93 days, 34.70 ± 0.45 days and 28.67 ± 0.46 days, respectively and tended to decrease with increasing temperature. A similar trend was observed for larvae and pupae development time. There was 100 % egg mortality at 15 °C and 40°C. Larval mortality was highest (46 %) at 35 °C and lowest (18 %) at 25°C. After emergence, adults had a pre-oviposition period that ranged from 5.73 ± 0.21 days at 30 oC to 16.17 ± 0.91 at 20°C. C.brunneus laid the highest number of eggs (93.67 ± 10.54 eggs) at 30°C and least eggs (26.33 ± 2.84 eggs) at 20°C. Based on these life table data, the optimal temperature for C. brunneus population growth and development was noted to be 25°C.